Research for CULT Committee - The EU’s approach to multilingualism in its own communication policy - Mendez, Carlos; Gazzola, Michele; Clement-Wilz, Laure; Triga, Vasiliki; Mendez, Fernando; Djouvas, Constantinos; Charalambous, Antonis; Bachtler, John (My University, 2022)
This study assesses the EU’s approach to multilingualism in its communications policy. An innovative mixed methods approach is used to investigate compliance with multilingualism obligations and the language regimes and practices of EU institutions, bodies and agencies, especially on EU websites. The fit with the linguistic skills of EU27 residents is also investigated. Policy recommendations are provided to enhance the transparency and accessibility of EU communication policy taking account of feasibility constraints.
Keywords: Multilingualism; Communications policy; European Union; Website analysis